Jenis – Jenis Tumbuhan Yang Digunakan Untuk Mengobati Penyakit Pada Manusia Oleh Masyarakat Desa Nunusunu Kecamatan Kualin Kabupaten Timor Tengah Selatan - Anayunita Pehuki; Lukas Seran; Maria Novita Inya Buku (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2023)
Local wisdom without using natural ingredients to treat human diseases in Nunusunu Village is still fragmentary (limited/known to certain people). Therefore, academic research needs to be carried out and published so that it is known by many people. This research aims to find out the types of medicinal plants used by the community, the parts of plants used as medicine, the types of diseases treated with medicinal plants, how to process medicinal plants, the types of medicinal plants that are most widely used, the types of medicinal plants cultivated and the reasons for medicinal plants. is cultivated. The type of research used is descriptive research. The method used in collecting data was by means of documentation and semi-structured interviews (attached). The results of the research found that there were 17 types of plants, namely: Taduk (Alstoniascholaris), Kapok (Ceibapentandra), Red spinach (Amaranthus tricolor L), Soursop (Annona muricata), Anonak (Annona feticulata), Kirinyuh (Chromolaenaodorata), Papaya ( Carica papaya), Guava (Psidiumguajava), Pomegranate (Punicagranatum), Betel leaf (Piper betle), Binahong (Anrederacordifolia), Lemongrass (Cymbopogoncitratus), Betadin / Jatropha tintir (Jatropha multifida), Moringa leaf (MoringaOleifera ), Mahogany (SwieteniaMahagoni), Aruda (Rutagraveolens), Red Damar (Jatropha). The parts of plants used/utilized as medicine are leaves, stems, seeds, rhizomes/roots. The method of processing/using medicinal plants is by eating them directly, boiling them, burning them, chewing them/pounding them. Types of human diseases that can be treated are back pain, boils, low blood pressure, cancer (uterine and breast), flatulence, bleeding wounds, sore/caved teeth, stomach ache, diarrhea, diabetes/white urine, stomach, tumors, cure external and internal wounds, high fever and worms, coughing, vomiting blood. The types of plants most widely used are red spinach, soursop, anonak, kirinyuh, betel leaf, binahong, lemongrass.The types of plants cultivated are binahong, lemongrass, lemongrass leaves, betel leaves, red spinach, moringa, papaya, pomegranate, soursop, anonak. The reason plants are cultivated is that apart from being medicines to treat diseases in humans, these plants can also be consumed by the public so they are cultivated so they are easy to find and use when needed.The conclusion of this research was that 17 types of plants were obtained. The parts of plants used are leaves, stems, seeds and roots. The method of processing/using medicinal plants is by eating them directly, boiling them, burning them, chewing them/pounding them. And the medicinal plants cultivated by the Nunusunu community are binahong, lemongrass, betel leaves, red spinach, moringa, papaya, pomegranate, soursop, anonak. The reason medicinal plants are cultivated is that apart from being a medicine to treat diseases in humans, these plants can also be consumed by the community. so it is cultivated to be easy to find and use when needed.